Highly Transparent Yb:Y2O3 Laser Ceramics with High Thermal Conductivity Obtained via a Sintering-Additive-Free Strategy - Zhongchao Fu; Qiang Wu; Nan Wu; Haibo Long; Jinsheng Li; Yi Ren; Zhaoxia Hou (Inorganics, 2025)
Fine-grained Yb:Y2O3 laser ceramics with excellent transmittance and thermal conductivity were fabricated from commercial powders. The process involved aqueous colloidal forming, additive-free air pre-sintering at 1400 °C, and hot isostatic pressing at 1550 °C. Suspensions were prepared with a deionization process to alleviate the hydrolysis issue, which optimizes the microstructure uniformity and enhances the green compacts’ density after consolidation. The microstructure, in-line transmittance, microhardness, and fracture toughness of the Yb3+-doped Y2O3 ceramics with different concentrations were measured. The 5.0 at% Yb3+-doped Y2O3 ceramic yielded a superior transmittance of 80.1% at 1100 nm and 83.0% in the mid-infrared region. The average grain size was 752 nm. The sample exhibited a thermal conductivity of 9.94 W·m−1·K−1 while achieving a 1076 nm laser output with a 42 mW peak power and 4.3% slope efficiency.